2021
DOI: 10.1186/s40634-021-00409-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific difference in the recurrence of flexion contracture after total knee arthroplasty

Abstract: Background Range of motion after total knee arthroplasty (TKA) can impact patients’ daily lives. Nevertheless, flexion contracture (FC) often recurs after TKA, even upon achieving full extension intraoperatively. This study aimed to evaluate the relationship among preoperative, intraoperative, and postoperative knee extension angles, and clarify the risk factor for postoperative FC. Methods One hundred forty-seven knees undergoing TKA using a navig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Five of the included studies [ 11 13 , 19 46 ] correlated patient preoperative factors with the incidence of postoperative flexion contracture. Predictors of postoperative flexion contracture were male gender, older age, and preoperative flexion contracture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the included studies [ 11 13 , 19 46 ] correlated patient preoperative factors with the incidence of postoperative flexion contracture. Predictors of postoperative flexion contracture were male gender, older age, and preoperative flexion contracture.…”
Section: Resultsmentioning
confidence: 99%
“…However, BMI was not a risk factor. Kinoshita et al [ 19 ] found a significantly greater risk of postoperative flexion in male patients with preoperative flexion. In contrast, a later study by Lustig et al [ 21 ] disagreed with all factors, finding no significant difference between patients with and without flexion contracture of at least 5° at one year postoperatively in terms of gender or age.…”
Section: Resultsmentioning
confidence: 99%
“…Only osteoarthritic patellae were resurfaced in our series and the difference in postoperative flexion was not significant. Other preoperative predictive factors as quadriceps weakness [17], kinematics [18], education level [19], gender [20], and hip stiffness [21] have been reported. Authors still claim that high knee flexion is not necessary for patient satisfation [22].…”
Section: Discussionmentioning
confidence: 98%
“…Although the CSRP type has no particular restrictions on the sagittal alignment of the femoral component, excessive exion insertion may cause postoperative exion contracture [43]. In particular, it has been reported that males are signi cantly more likely to develop postoperative exion contracture of 5 °after TKA than females are [44].…”
Section: Discussionmentioning
confidence: 99%